L’atome d’hydrogène sous L’action d’un multi-potentiel dans l’espace – temps non commutatif à deux dimensions - ELBAHI, FATIMA (Université Mohamed BOUDIAF de M'Sila, 2014)
In this work of search we have studied, in master theoretical physics, option: of particles physics at high energy, the effect of the non commutativity to the Schrödinger equation with multi-potential in two dimensional spaces with Boopp’s shift method. We applied perturbation theory to find modification of energy levels; we formed the deformed Hamiltonian which described automatically the new Zeeman Effect, including usual Zeeman.
Keywords: Hydrogen atom, non commutative space, Schrödinger equation, Hamiltonian, magnetic field, Zeeman Effect, multi-potential